Culture Based Counseling Communication Skill Development Module - Ilyas, Sabrida M; Chalidaziah, Wan (Jurnal Neo Konseling, 2022)
guide in improving culture-based counseling communication skills for guidance and counseling students and to describe the level of its application by lecturers of counseling communication courses in guidance and counseling service units at universities. This research method uses the ADDIE Research and Development model (Analyze, Design, Development, Implementation, and Evaluation). The research was conducted by testing research products in the form of modules and continued with discussion group forums (FGD) and data were analyzed using descriptive and inferential analysis. The results showed that the culture-based counseling communication skills module was at an average value of 4.80 and the usability test result was 4.33, which means that the module product designed is very feasible and can be used and passed the usability test by counseling experts. Furthermore, the culture-based counseling communication skills module can be used in learning for guidance and counseling students who have different cultural backgrounds.